PENERAPAN STRATEGI BELAJAR AKTIF TIPE GROUP TO GROUP DIIRINGI COLLEGE BALL PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMP N 3 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Putri, Lara Mulya; ZA, Nilawasti; K, Delsi. (STKIP PGRI Sumbar, 2013)
The background of this research is studentâs achievement in mathematic is law under the KKM (minimal achievement criteria), This probiem caused by the studentâs understanding about the concept mathematic they lost the concept in their memory quickly. The purpose of the research to know is the student achievement in mathematic by using Group To Group active learning strategy and College Ball better than convensional learning for students grade VIIIÂ SMPN 3 Koto XI Tarusan in 2011/-2013.The type of research is experimental. The study population were studentâs of class VIII SMPN 3 Koto XI Tarusan in 2012/2013. Technique of random sampling. This research instrument is the achievement test. The form used is the essay test, a reliability test r11= 0,72. The data analysis technique used is t-test of one part with the help of software MINITAB. The result of hypothesis test obtained P-Value = 0,009 is less than Î± = 0,05, then the hypothesis in this research received. In conclusion, studentâs achievement in mathematic by using Group To Group active learning strategy and College BallÂ better than conventional learning